Formação continuada de professores indígenas do alto Rio Negro em educação em saúde bucal - Leiria, Laís Vilhena (2020)
Education in oral health requires an expanded approach to the health-disease-care process and, above all, multidisciplinary strategies, involving various professionals and social institutions, including the school. However, in the case of indigenous peoples, this model of care must go beyond the prevention of oral diseases, and it is also important to develop the subjects' autonomy and reduce risks through health promotion actions. This research aimed to investigate in which aspects a continuing education course in Oral Health Education can collaborate in the process of reflection of the indigenous teacher from Alto Rio Negro regarding his educational practice in oral health at school. The research participants were four indigenous teachers who work in basic education, in a school in the Ilha das Flores community, in the municipality of São Gabriel da Cachoeira, Amazon. It was a qualitative research, using action research (TRIPP, 2005) as a method for the development of continuing education, with a workload of 20 hours, structured in three phases: planning; implementation and evaluation. As data collection techniques, we used the focus group and observation; and as instruments for recording data, we use the session reports, audio and video recordings and productions of the participants (notebook with written records, drawings and teaching materials). The data were organized and interpreted through the Discursive Textual Analysis (MORAES; GALIAZZI, 2011), and pointed out four aspects: 1) the rescue of the discussion about the discontinuity of oral health education actions at school; 2) the teacher's role during the training course; 3) the joint actions of education and health in the village, represented symbolically, by the union of three hills: education, indigenous mythology and health and; 4) the reflection of the educational practice in oral health at school revealed through concepts, procedures and attitudes of teachers during the training. This research resulted in the educational product, “It's time for Aru: new winds for Oral Health Education in indigenous schools”.